Quinary numbering system, in motifs 19, 20 and 21 of sector D in Quilla Rumi, Huanuco - Alomia-Lucero, José M. (2024)
Quilla Rumi houses more than 200 cave paintings that have not yet been deciphered, which opens the possibility of analyzing them from a scientific approach to deepen the knowledge of the first inhabitants and their cultural identity in relation to the historical past of Huánuco. The purpose of the study was to demonstrate that motifs 19, 20 and 21 of sector D in Quilla Rumi represent the quinary numbering system of the ancient settlers of the region. A qualitative approach, documentary type and analytical-synthetic methods were used to analyze the images of the cave paintings. The analysis of these three motives revealed their interrelationships. It is concluded that motif 20, with four points and a line, represents the number five, considered as a hand in the quinary number system. The 21 motif, with a square and a central dot, also symbolizes the number five, but in a more advanced and practical way. Motif 19 represents the number 25 or five hands, and by including the head with two eyes and a nose, it could represent 28 days, the lunar cycle. Furthermore, the head of the figure is identified as that of a Peruvian dog due to its morphological characteristics.